(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The Kelantan kelingkan embroidery has been a creation of Malay art of fashion for ages. The application of various motifs of flora and fauna using gold and silver thread embroidery makes kelingkan a beautiful and exclusive clothing. This article aims to identify the presence of the various flora and fauna motifs and its functions, as well as analyze the elements of the flora and fauna in the art of kelingkan embroidery using the Aesthetic Approach to Malay Arts by Zakaria Ali (1989). This study used two main methods, namely library research and field research, by interviewing practitioners or experts in kelingkan embroidery, especially in the state of Kelantan. The observation method was also used for the operation of the kelingkan embroidery workshop that is implemented at the National Craft Complex, Jalan Conlay, Kuala Lumpur. This study focused on the principles of the Aesthetic Approach to Malay Arts to analyze the use of flora and fauna motifs in order to highlight the Malay values of beauty. The findings suggest that Kelantan kelingkan embroidery has implemented motifs of flora and fauna in line with the six principles of the Aesthetic Approach to Malay Arts. The values of beauty and aesthetics that are shown through the implementation of flora and fauna motifs in the art of Kelantan kelingkan showcase the uniqueness and distinctiveness of the Malay thought itself in the production of traditional Malay art of fashion.